Factors influencing the purchase intention of green products among gen Z in Malaysia - Soo, Wan Rou; Gong, Steven Lian Kang (2023)
The purpose of this study is to understand the factors that influence the purchase intention of green products among Gen Z in Malaysia. A conceptual framework of theory of planned behaviour (TPB) and value belief norm theory (VBN) is used to study this topic. Our study consists of four independent variables (IV); attitude (ATT), subjective norms (SN), perceived behavioural control (PBC) and personal value (PV). All these IVs are used to study whether they can influence the dependent variable (DV) which is purchase intention of green products. A total of 308 responds were collected through the survey and the data were analyzed using Statistical Software Package for Social Sciences (SPSS). The findings of this study found out that three IVs attitude (ATT), perceived behavioural control (PBC), personal value (PV) have significant relationship towards the DV (purchase intention). However, the subjective norms (SN) do not have significant relationship with the DV (purchase intention). This study helps the researchers to further understand the factors that influence the purchase intention of green products among Gen Z in Malaysia.